2017
DOI: 10.1039/c7tc00189d
|View full text |Cite
|
Sign up to set email alerts
|

The impact of aggregation on the p-doping kinetics of poly(3-hexylthiophene)

Abstract: The morphological effects of regioregular poly(3-hexylthiophene) (P3HT) on its p-doping kinetics with 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4-TCNQ) in solution are studied using optical absorption spectroscopy and stopped-flow technique. Two morphological forms, solubilized (s-P3HT) and nanowhiskers (nw-P3HT), are investigated. Both P3HT solubilized and aggregated solutions show similar characteristic near-IR absorption bands for integer charge transfer products with F4-TCNQ. Kinetic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…Given the relationship between conductivity, σ, charge density, n , and mobility, μ, (σ = neμ ), we obtain a value of μ AC = 0.0154 ± 0.00383 cm 2 V −1 s −1 from a straight line fit to the, above‐threshold, linear region of σ versus n in Figure b. This mobility is the isotropic value (average over three dimensions) although we expect charge motion to mostly confined to lamellae, being fastest along the chain (crystallographic c axis) or in the π–π stacking direction ( b axis), along the long axis of the nanowire; conductive atomic force microscopy studies[19a,22b] have shown the transport along the a axis to be three to four orders of magnitude slower.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…Given the relationship between conductivity, σ, charge density, n , and mobility, μ, (σ = neμ ), we obtain a value of μ AC = 0.0154 ± 0.00383 cm 2 V −1 s −1 from a straight line fit to the, above‐threshold, linear region of σ versus n in Figure b. This mobility is the isotropic value (average over three dimensions) although we expect charge motion to mostly confined to lamellae, being fastest along the chain (crystallographic c axis) or in the π–π stacking direction ( b axis), along the long axis of the nanowire; conductive atomic force microscopy studies[19a,22b] have shown the transport along the a axis to be three to four orders of magnitude slower.…”
mentioning
confidence: 87%
“…This aggregation lowers the oxidation potential of the polymer, allowing for increased reactivity with dopants . Doping induces aggregation in P3HT both kinetically and thermodynamically, through increased planarity of the polymer cation, and increased hole delocalization, respectively . We seek to understand if P3HT aggregates enable unprecedented ion pair dissociation constants in nonpolar media.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular doping is an effective way to increase the conductivity of organic semiconductors [8][9][10] . Over the years, P3HT doped by F4TCNQ has become the field's fruit fly system, and the doping mechanism and kinetics have been researched by several groups [11][12][13][14][15] . In conventional solution processing the doped layer is deposited from a common solution containing both the semiconductor (P3HT) and the dopant (F4TCNQ) -in the following we shall refer to this as bulk doping.…”
mentioning
confidence: 99%